2021
DOI: 10.1080/17843286.2021.1940776
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the FREND™ COVID-19 IgG/IgM Duo point-of-care test for SARS-CoV-2 antibody detection

Abstract: Purpose : In the context of the current COVID-19 pandemic, multiple serological assays for the detection of severe acute respiratory syndrome 2 (SARS-CoV-2) immune response are currently being developed. This study compares the FREND TM COVID-19 IgG/IgM Duo (NanoEntec) a point of care (POCT) assay with the automated Elecsys anti-SARS-CoV-2 electrochemiluminescent assay (Roche Diagnostics). Methods: Serum samples ( n = 81) from PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Regarding serological tests POC and RDT for detecting antibodies, most showed high sensitivity and specificity values, indicating good clinical performance. However, we observed lower sensitivity values in tests that performed the analysis in the first days after SARS-CoV-2 infection [57,61,62,64] than in postinfection studies.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Regarding serological tests POC and RDT for detecting antibodies, most showed high sensitivity and specificity values, indicating good clinical performance. However, we observed lower sensitivity values in tests that performed the analysis in the first days after SARS-CoV-2 infection [57,61,62,64] than in postinfection studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Among the 13 selected studies, 10 presented high values of sensitivity and specificity (>80%) [56][57][58]60,61,[64][65][66][67][68], and 1 reported 100% of sensitivity and specificity [56]. Lower sensitivity values were observed in the first days after infection [57,61,62,64] than the days postinfection. Accuracy was reported in three studies [56,63,65], and values lower than 80% were found only in the study by Fauziah et al [62].…”
Section: Immunoglobulin Detection Testsmentioning
confidence: 99%
See 1 more Smart Citation